Analysis of Factors that Cause Students not to Continue Education in Higher Education - Mohammad Amin Lasaiba; Djamila Lasaiba (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
This study aims to determine the factors that cause high school graduate students not to continue their studies to college at SMA N 1 Leihitu. the type of research used is quantitative using descriptive analysis techniques. The sample in this study amounted to 62 people who were randomly selected for graduate students in 2020, 2021, and 2022. The results of this study indicate that the dominant factor that causes high school graduate students not to continue their studies to college is the economic factor, in which the economic factor gets the results were 39 respondents, or 62.9% of the 62 respondents stated that economic factors were the cause of not continuing their studies to college, then the interest factor which got results was 36 respondents or 39.13% of 62 respondents and social factors which were only 34 respondents or 17.39% of the 62 respondents. From the results of the analysis, it was concluded that economic factors were the main cause of high school graduates not continuing their studies to college with a percentage yield of 62.9%.